Draft Genome Sequence of the Extremophile Acidithiobacillus thiooxidans A01, Isolated from the Wastewater of a Coal Dump - Yin, Huaqun (American Society for Microbiology, 2014)
The draft genome of Acidithiobacillus thiooxidans A01 contains 3,820,158 bp, with a G+C content of 53.08% and 3,660 predicted coding sequences (CDSs). The bacterium contains a series of specific genes involved in the oxidation of elemental sulfur and reduced inorganic sulfur compounds (RISCs).